Stress and quality of working life : current perspectives in occupational health - Rossi, Ana Maria; Perrewé, Pamela L.; Sauter, Steven L., 1946- (Emerald Publishing Limited : Information Age Pub., 2006)
This is the eighth edition of the Stress and Quality of Working Life book series. The Brazilian section of the International Stress Management Association (ISMA-BR), a not-for-profit organization that studies stress and ways to prevent it, together with two renowned American researchers, has organized the eighth volume of the series Stress and Quality of Working Life: Coping at Work and at Home. The new volume offers some of the latest theories and methods on how to cope with stress and quality of working life issues based on the experience and knowledge of recognized international experts in this field. This book is meant to be a tool to provide information and suggest ways to deal with pressures and demands from the workplace.The contemporary workplace includes a combination of traditional workplace environments, work-from-home arrangements, and hybrid models with some combination of working from a traditional environment and at home. Our authorship team comprises international experts from many disciplines so we can provide insights into contemporary stress and quality of working life issues, as well as how to cope with them at work and at home.
"This book was developed for the 2005 International Stress Management Association Conference in Brazil"--page vii.
Keywords: Job stress -- Congresses.; elektronické knihy; Conference papers and proceedings.; Business & Economics -- Workplace Culture.; Office and workplace.; Working patterns and practices.; electronic books